Acid-base and lipophilic properties of peptide nucleic acid derivatives - Pramod Thakare; Francesca Vasile; Maura Vallaro; Sonja Visentin; Giulia Caron; Emanuela Licandro; Silvia Cauteruccio (Elsevier, 2021)
The first combined experimental and theoretical study on the ionization and lipophilic properties of peptide nucleic acid (PNA) derivatives, including eleven PNA monomers and two PNA decamers, is described. The acidity constants (pKa) of individual acidic and basic centers of PNA monomers were measured by automated potentiometric pH titrations in water/methanol solution, and these values were found to be in agreement with those obtained by MoKa software. These results indicate that single nucleobases do not change their pKa values when included in PNA monomers and oligomers. In addition, immobilized artificial membrane chromatography was employed to evaluate the lipophilic properties of PNA monomers and oligomers, which showed the PNA derivatives had poor affinity towards membrane phospholipids, and confirmed their scarce cell penetrating ability. Overall, our study not only is of potential relevance to evaluate the pharmacokinetic properties of PNA, but also constitutes a reliable basis to properly modify PNA to obtain mimics with enhanced cell penetration properties.